If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+6(3x-9)+21=63
We move all terms to the left:
4x+6(3x-9)+21-(63)=0
We add all the numbers together, and all the variables
4x+6(3x-9)-42=0
We multiply parentheses
4x+18x-54-42=0
We add all the numbers together, and all the variables
22x-96=0
We move all terms containing x to the left, all other terms to the right
22x=96
x=96/22
x=4+4/11
| 12x=-204 | | 4n+16=5(6n-2) | | 9p−6=10p | | 1/2x+.3333333=3x-3 | | b+6=7(6b-5) | | −20=−4x-6x | | G(-2)=x2-2x | | )7x-10x+18+2x=-5 | | 11+3n=1+n | | 5(2x+8)=-4(x+11) | | y+y+y+y=600 | | 2n-(-3.31)=12.51 | | -n-5=8n-4n | | 3+6t=5 | | B*C=11+2x | | 8x+23x-14-2x=14x+31 | | 2b+4.8=16.8 | | C=11+2x | | -3p=6-5p | | -2(v-2)=- | | 4.8+9.8x+9=3.8x-16+3.8x | | 18.84-11t=18.13-3.9t | | − | | − | | − | | n+5=-15-3n | | 1.1n+1.5n−5.6=-16 | | 4x/3+2(x-3)+7=31 | | 8+(-3f)=5 | | F(10)=2x-4 | | 8+(-3f(=5 | | 4-n=-14-4n |